The Implications of Zinc Therapy in Combating the COVID-19 Global Pandemic - Samad N; Sodunke TE; Abubakar AR; Jahan I; Sharma P; Islam S; Dutta S; Haque M (Dove Medical Press, 2021)
Nandeeta Samad,1 Temitayo Eniola Sodunke,2 Abdullahi Rabiu Abubakar,3 Iffat Jahan,4 Paras Sharma,5 Salequl Islam,6 Siddhartha Dutta,7 Mainul Haque8 1Department of Public Health, North South University, Dhaka, 1229, Bangladesh; 2Department of Anatomy, University of Ilorin, Ilorin, Kwara State, Nigeria; 3Department of Pharmacology and Therapeutics, Faculty of Pharmaceutical Sciences, Bayero University, Kano, 700233, Nigeria; 4Department of Physiology, Eastern Medical College, Cumilla, Bangladesh; 5Department of Pharmacognosy, BVM College of Pharmacy, Gwalior, India; 6Department of Microbiology, Jahangirnagar University, Dhaka, 1342, Bangladesh; 7Department of Pharmacology, All India Institute of Medical Sciences, Jodhpur, Rajasthan, India; 8The Unit of Pharmacology, Faculty of Medicine and Defence Health, Universiti Pertahanan Nasional Malaysia (National Defence University of Malaysia), Kuala Lumpur, MalaysiaCorrespondence: Mainul HaqueUnit of Pharmacology, Faculty of Medicine and Defence Health, Universiti Pertahanan Nasional Malaysia (National Defence University of Malaysia), Kem Perdana Sungai Besi, Kuala Lumpur, 57000, MalaysiaTel +60 10 926 5543Email runurono@gmail.comAbstract: The global pandemic from COVID-19 infection has generated significant public health concerns, both health-wise and economically. There is no specific pharmacological antiviral therapeutic option to date available for COVID-19 management. Also, there is an urgent need to discover effective medicines, prevention, and control methods because of the harsh death toll from this novel coronavirus infection. Acute respiratory tract infections, significantly lower respiratory tract infections, and pneumonia are the primary cause of millions of deaths worldwide. The role of micronutrients, including trace elements, boosted the human immune system and was well established. Several vitamins such as vitamin A, B6, B12, C, D, E, and folate; microelement including zinc, iron, selenium, magnesium, and copper; omega-3 fatty acids as eicosapentaenoic acid and docosahexaenoic acid plays essential physiological roles in promoting the immune system. Furthermore, zinc is an indispensable microelement essential for a thorough enzymatic physiological process. It also helps regulate gene-transcription such as DNA replication, RNA transcription, cell division, and cell activation in the human biological system. Subsequently, zinc, together with natural scavenger cells and neutrophils, are also involved in developing cells responsible for regulating nonspecific immunity. The modern food habit often promotes zinc deficiency; as such, quite a few COVID-19 patients presented to hospitals were frequently diagnosed as zinc deficient. Earlier studies documented that zinc deficiency predisposes patients to a viral infection such as herpes simplex, common cold, hepatitis C, severe acute respiratory syndrome coronavirus (SARS-CoV-1), the human immunodeficiency virus (HIV) because of reducing antiviral immunity. This manuscript aimed to discuss the various roles played by zinc in the management of COVID-19 infection.Keywords: zinc therapy, microelement, immune-boosting, efficacy, COVID-19, viral infections, pneumonia, pandemic